Online Loans In Islamic Perspective Literature Analysis On Law, Impact, And Solutions - Fahrurrozi, Muhammad; Fikriyah, Khusnul (GERASI INSAN NUSANTARA, 2024)
Online loans have become a global phenomenon, including in Indonesia, with rapid growth due to easy access and fast processes. However, the practice of online loans is often associated with issues of usury, exploitation, and violations of sharia. This study aims to analyze online loans from an Islamic perspective through a literature approach by reviewing sources of the Qur'an, Hadith, fatwas of scholars, and sharia financial regulations. The results of the study indicate that online loans containing elements of usury and gharar (unclarity) are prohibited in Islam, while sharia online loans based on the principle of profit sharing (mudharabah/qardhul hasan) is permitted. This article also discusses the socio-economic impacts of online loans and Islamic solutions to avoid practices that conflict with sharia